W ' expenditure and reconstitution during severe intensity constant power exercise: mechanistic insight into the determinants of W ' - Broxterman, R. M.; Skiba, P. F.; Craig, J. C.; Wilcox, S. L.; Ade, Carl J.; Barstow, Thomas J. (My University, 2017)
The sustainable duration of severe intensity exercise is well-predicted by critical power (CP) and the curvature constant (W'). The development of the W-BAL' model allows for the pattern of W' expenditure and reconstitution to be characterized and this model has been applied to intermittent exercise protocols. The purpose of this investigation was to assess the influence of relaxation phase duration and exercise intensity on W' reconstitution during dynamic constant power severe intensity exercise. Six men (24.6 +/- 0.9 years, height: 173.5 +/- 1.9 cm, body mass: 78.9 +/- 5.6 kg) performed severe intensity dynamic handgrip exercise to task failure using 50% and 20% duty cycles. The W-BAL' model was fit to each exercise test and the time constant for W' reconstitution (tau(W)') was determined. The sW' was significantly longer for the 50% duty cycle (1640 +/- 262 sec) than the 20% duty cycle (863 +/- 84 sec, P = 0.02). Additionally, the relationship between sW' and CP was well described as an exponential decay (r(2) = 0.90, P < 0.0001). In conclusion, the W-BAL' model is able to characterize the expenditure and reconstitution of W' across the contraction-relaxation cycles comprising severe intensity constant power handgrip exercise. Moreover, the reconstitution of W' during constant power severe intensity exercise is influenced by the relative exercise intensity, the duration of relaxation between contractions, and CP.
Citation: Broxterman, R. M., Skiba, P. F., Craig, J. C., Wilcox, S. L., Ade, C. J., & Barstow, T. J. (2016). W ' expenditure and reconstitution during severe intensity constant power exercise: mechanistic insight into the determinants of W '. Physiological Reports, 4(19), 9. doi:10.14814/phy2.12856
Keywords: Critical Power; Exercise Tolerance; Modeling; W '; Blood-Flow Occlusion; Duration Relationship